2007
DOI: 10.1038/sj.onc.1210530
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-associated genes are extremely poor prognostic factors for soft-tissue sarcoma patients

Abstract: Cancer stem cells can play an important role in tumorigenesis and tumor progression. However, it is still difficult to detect and isolate cancer stem cells. An alternative approach is to analyse stem cell-associated gene expression. We investigated the coexpression of three stem cell-associated genes, Hiwi, hTERT and survivin, by quantitative real-time-PCR in 104 primary soft-tissue sarcomas (STS). Multivariate Cox's proportional hazards regression analyses allowed correlating gene expression with overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 19 publications
(30 reference statements)
9
40
0
Order By: Relevance
“…Because of the primitive appearance of these neoplasms, we investigated expression of several markers that characterize stem cells, including survivin, CD117, CD105, and nestin [22][23][24]. Survivin, a member of the inhibitors of apoptosis gene family, is highly expressed in embryonal tissues and is a marker of aggressive clinical behavior in sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the primitive appearance of these neoplasms, we investigated expression of several markers that characterize stem cells, including survivin, CD117, CD105, and nestin [22][23][24]. Survivin, a member of the inhibitors of apoptosis gene family, is highly expressed in embryonal tissues and is a marker of aggressive clinical behavior in sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…4). It would be of interest if genes associated with (cancer) stem cell self-renewal, which also have prognostic impact for cancer patients (28), play a role in disseminated tumor cell/circulating tumor cell dormancy. Meng and colleagues (29) showed that uPAR and ERBB2/HER-2 gene status in breast cancer cells from blood and tumor tissue are concordant.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Piwi,theDrosophilahomologue,resultsinanincreaseboth inthenumberofgermlinestemcellsandtherateoftheir divisions [25].ElevatedexpressionofMili,oneof3mouse Piwi homologues, inhibits apoptosis and stimulates proliferation [26].ExpressionofHiwihasbeenreportedinseminomas, gastric carcinomas, and soft-tissue sarcoma (STS) [25,27,28]. There was an association between altered expression of Hiwi mRNA and a poor prognosis for STS patients [29].…”
Section: Introductionmentioning
confidence: 99%